OMFS moving into the recovery phase of the COVID-19 pandemic – a survey on general practice for elective local anaesthetic procedures. Issue 8 (October 2020) - Graham, C.; Mizen, K.D.
Abstract: The COVID-19 pandemic has meant a halt to elective oral and maxillofacial procedures under local anaesthetic. As oral and maxillofacial departments enter the recovery phase of the COVID-19 pandemic there are many considerations to make regarding standard operating procedures. Thus, this survey was conducted to identify areas of consensus and divergence in practice during the recovery phase of the pandemic for local anaesthetic procedures in oral and maxillofacial units. Our findings show there are some areas of inconsistency of practice particularly in preoperative risk management and self-isolation as well as fallow time between patients for aerosol generated procedures and non-aerosol generated procedures.